LUMEN: Prototype Conversational AI to Streamline Dementia Assessments - Song Ling Tang; Alexander Robertson; Huizhi Liang; John-Paul Taylor; Judith Harrison (BJPsych Open, 2025)
Aims: Dementia assessments are time-intensive and often distressing for patients and caregivers. Underdiagnosis of non-Alzheimer’s disease subtypes remains prevalent. This study aimed to develop and evaluate LUMEN (Large Language Model for Understanding and Monitoring Elderly Neurocognition), a prototype conversational AI to automate caregiver-collateral data collection before clinical appointments. Our goals were to reduce clinician time per assessment, improve diagnostic accuracy across dementia subtypes, and standardise caregiver assessments.